Ultra‐High Initial Coulombic Efficiency Induced by Interface Engineering Enables Rapid, Stable Sodium Storage. Issue 20 (6th April 2021) - Wan, Yanhua; Song, Keming; Chen, Weihua; Qin, Changdong; Zhang, Xixue; Zhang, Jiyu; Dai, Hongliu; Hu, Zhe; Yan, Pengfei; Liu, Chuntai; Sun, Shuhui; Chou, Shu‐Lei; et al.
Abstract: High initial coulombic efficiency is highly desired because it implies effective interface construction and few electrolyte consumption, indicating enhanced batteries' life and power output. In this work, a high‐capacity sodium storage material with FeS2 nanoclusters (≈1–2 nm) embedded in N, S‐doped carbon matrix (FeS2 /N, S‐C) was synthesized, the surface of which displays defects‐repaired characteristic and detectable dot‐matrix distributed Fe‐N‐C/Fe‐S‐C bonds. After the initial discharging process, the uniform ultra‐thin NaF‐rich (≈6.0 nm) solid electrolyte interphase was obtained, thereby achieving verifiable ultra‐high initial coulombic efficiency (≈92 %). The defects‐repaired surface provides perfect platform, and the catalysis of dot‐matrix distributed Fe‐N‐C/Fe‐S‐C bonds to the rapid decomposing of NaSO3 CF3 and diethylene glycol dimethyl ether successfully accelerate the building of two‐dimensional ultra‐thin solid electrolyte interphase. DFT calculations further confirmed the catalysis mechanism. As a result, the constructed FeS2 /N, S‐C provides high reversible capacity (749.6 mAh g −1 at 0.1 A g −1 ) and outstanding cycle stability (92.7 %, 10 000 cycles, 10.0 A g −1 ). Especially, at −15 °C, it also obtains a reversible capacity of 211.7 mAh g −1 at 10.0 A g −1 . Assembled pouch‐type cell performs potential application. The insight in this work provides a bright way to interface design for performance improvement in batteries. Abstract : A defect‐repairing‐induced dot–matrix distributed interface efficiently catalyzes electrolyte decomposition. This strategy enables an ultra‐thin and robust solid–electrolyte interface achieving ultra‐high initial coulombic efficiency in sodium‐ion batteries.